Determinan Faktor Kepatuhan Pengunjung dalam Penerapan Protokol Kesehatan di Ruang Perinatologi RSUD Bali Mandara - Ni Kadek Yoni Wedyandhari; Ni Made Ari Sukmandari; Ni Putu Dita Wulandari (JURNAL MEDIKA USADA, 2023)
The end of 2019 to the beginning of 2022, the world is experiencing major health problems with an incident that makes people nervous, namely a new virus known as Coronavirus Disease From 2019 (Covid-19). Compliance with the 5M health protocol is important to prevent transmission of the Covid-19 virus. The purpose of this study was to determine the determinants of factors related to visitor compliance in implementing health protocols in the Perinatology Room of Bali Mandara Hospital. This type of research is descriptive analytic with cross sectional approach. The sampling technique used is a non-probability sampling technique with a purposive sampling approach. The sample in this research is 56 respondents. The data collection instrument used in this study was a health protocol adherence questionnaire which was declared valid and reliable. Data were analyzed using Kruskall Wallis test for bivariate analysis and logistic regression test for multivariate analysis. Factors related to visitor compliance in implementing health protocols in the Perinatology Room of the Bali Mandara Hospital, namely age, gender and education.Based on the multivariate analysis, the most dominant factor was gender with an odds ratio of 32.018 which meant that there was a tendency for women to have compliance 32.018 or 32 times higher than men. People with the male gender need to increase adherence to implementing health protocols.